FAKTORâFAKTOR PENENTU TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) (Studi Empiris Pada Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2013-2015) - Anggun Widita, 13.05.52.0229; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of the size of local government, independence ratio, functional differentiation, debt financing, intergovernmental revenue, the life of the local government, and the size of the legislature on the level of disclosure LKPD Regency / City in Central Java province. The study population was District / City of Central Java Province during the years 2013- 2015 which had been audited by the BPK. Samples were included in the research criteria inisebanyak 35 districts / cities in Central Java Province using purposive sampling method. The results showed that the variable size of local government debt financing and the life of local governments significant positive effect on the level of disclosure LKPD while the ratio of self-sufficiency, functional differentiation, intergovernmental revenue, and a legislative measure does not affect the level of disclosure LKPD.Keywords: Level of Disclosure LKPD, Local Government Size, Ratio Independence, Functional Differentiation, The Intergovernmental Revenue, Local Government Age and Size of The Legislature